Students' Perceptions of The Digital Media Used By English Lecturers on Teaching English - Alavi Muhammad Farenzi; Lisa Rakhmanina; Melati, Melati (Edu-Ling: Journal of English Education and Linguistics, 2024)
The rapid integration of digital media in education has transformed teaching and learning processes, particularly in English language instruction. This reserach investigates students’ perceptions of the digital media utilized by English lecturers in teaching English, focusing on its effectiveness, accessibility, and impact on learning outcomes. Employing qualitative descriptive methodology data were collected through questionnaires and interviews. The results show that Spada Unihaz is the most frequently used media for learning English, with 80% usage. Students also use other platforms like Zoom, WhatsApp Group, and Google Classroom. Most students (95%) believe digital media helps improve their English skills, with 77.8% believing it improves speaking, 88.9% listening, 83.7% writing, and 82.2% reading skills. However, 85.4% of students face technical difficulties and lack of guidance. Despite these challenges, 95.3% of students prepared themselves before class and felt the facilities supported their learning process. However, challenges such as technical issues, inconsistent usage, and the digital divide were also highlighted. The reserach underscores the importance of selecting appropriate digital tools and offering adequate training to maximize their potential. These results have implications for English lecturers, suggesting the need for strategic integration of digital media in teaching practices to foster effective and inclusive language learning environments. The reserach concludes that while digital media is beneficial, it still presents challenges that need to be resolved for optimal effectiveness.